Penegakan Peraturan, Keefektifan Pengendalian Internal, Asimetri Informasi dan keadilan kompensasi Dalam Mempengaruhi Kecenderungan Fraud Pengadaan Barang/Jasa Pada Pemerintah Kota Surakarta - Denny Mahendra; Jarot Santosa; Aris Tri Haryanto (AKTUAL, 2019)
The purpose of this study was to determine and test the effect of the influence of enforcement, the effectiveness of internal control, information asymmetry and fairness of compensation for the tendency of goods / services procurement fraud in the Surakarta City Government. The population in this study were all employees of goods / services procurement officials at government agencies in the City Government of Surakarta, totaling 216 employees. The sampling method is simple random sampling. The sample used was 55 respondents. The analysis technique uses multiple linear regression in SPSS 20. The results of the study show that the enforcement of regulations and the effectiveness of internal control have no significant positive effect on fraud trends (Fraud). Information asymmetry and fair compensation have a significant positive effect on fraud (Fraud). Information asymmetry is the most dominant variable in influencing the tendency of fraud (fraud).Keywords: Enforcement of Regulations, Effectiveness of Internal Control, Information Asymmetry, Compensatory Justice, Fraud Trends in Procurement of Goods / Services